We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
219
1
avatar

Solve the equation. 

 

(1/3)lnx + ln2 - ln3 = 3

 Mar 5, 2018
 #1
avatar+18133 
+1

Couple of ways to go about this...let's do it the easy way

 

1/3 lnx + .69315 - 1.0986 =3      Simplify5

 

1/3 ln x = 3.4055

ln x = 10.164

x =  27346.67

 

 

 

ANOTHER way

ln (((x^1/3) (2)) /3) = 3

(x^1/3  *2)/3 = e^3

x^1/3 =  3/2  *  e^3

x  =  (3/2 * e^3 )^3 = 27347. 9    (difference due to rounding in the first example)

 Mar 5, 2018

35 Online Users

avatar
avatar
avatar
avatar